Análise experimental da operação de substituição do R22 do sistema de refrigeração operando com compressor scroll - Panato, Victor Hugo (2015)
This works focus on practical solutions for cooling systems that contribute to solve the problem of environmental degradation. The aim is to change the original cooling system working fluid, and identify in the universe of choices, the best alternative fluid. Thus, a experimental facility was built and, is consisted of a scroll compressor with capacity of 12 kW, originally designed for R22, as well as tube-in-tube heat exchangers and an electronic expansion valve (VEE). The system was properly instrumented, in order to enable the assessment of cooling capacity and COP. Each replacement on the original system, so, each drop-in process, contributes to confirming the uniqueness of the scroll compressor applications. In the beginning, tests were carried out to build the response surface and metamodels, so enable analyze the system boundaries. After this, new tests were carried out in all operation range. Starting with the operation frequency of 60 Hz and 100% opening VEE. Later, the boundaries of each the alternative refrigerant were tested. The results showed restriction to the type of fluid tested as well as to the operating conditions of the vapor compression cycle. The hydrocarbon (HC) R1270 operated in a limited conditions whereas R410A even reached steady state conditions. Refrigerants that showed better adaptation to the cooling system were HFCs R404A, R438A and R134a. In sequence, it was conducted performance analysis for each refrigerant operating with 90% of initial charge. As a result it was achieved a slight expansion of the system application region, however, the COP values were the lowest ones, except for the R404A. Finally, the estimation of environmental impacts of each fluid was calculated by the TEWI method. The R1270, even with operating limitations, showed the best results, while the R438A presented the worst result for the environment.